1994
DOI: 10.1037/0021-9010.79.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Further assessments of Meyer and Allen's (1991) three-component model of organizational commitment.

Abstract: The construct validity of J. P. Meyer and N. J. Allen's (1991) 3-component model of organizational commitment was assessed. Despite the large error components associated with some of the items from Meyer and Allen's scales, the existence of 3 facets of commitment (affective, continuance, and normative) was generally supported by a confirmatory factor analysis of data from 2,301 nurses. Moreover, some of the expected differential relationships of these facets to antecedents and outcomes of commitment were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
299
6
35

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(362 citation statements)
references
References 33 publications
(88 reference statements)
22
299
6
35
Order By: Relevance
“…ISSN 2162-4860 2015 variables that are potential antecedents, correlates, or consequences of commitment. As a general result, these studies have documented a high predictive power of commitment regarding turnover decisions, absenteeism, job satisfaction, and job performance (Mathieu & Zajac, 1990;Meyer & Allen, 1991;Meyer et al, 1993;Hackett et al, 1994;Meyer et al, 2002), and many of them have provided empirical support to the three-component specification of organizational commitment (Meyer et al, 1993;Hackett et al, 1994;Meyer et al, 2002). A robust result concerning the predictive power of the three components that has been pointed out by Meyer & Herscovitch (2001) and confirmed by the meta-analysis of Meyer et al (2002) is that "compared to continuance and normative commitment, affective commitment (a) correlates significantly with a wider range of "outcome" measures and (b) correlates most strongly with any given outcome measure" (Meyer & Herscovitch, 2001, p. 311).…”
Section: Affective Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSN 2162-4860 2015 variables that are potential antecedents, correlates, or consequences of commitment. As a general result, these studies have documented a high predictive power of commitment regarding turnover decisions, absenteeism, job satisfaction, and job performance (Mathieu & Zajac, 1990;Meyer & Allen, 1991;Meyer et al, 1993;Hackett et al, 1994;Meyer et al, 2002), and many of them have provided empirical support to the three-component specification of organizational commitment (Meyer et al, 1993;Hackett et al, 1994;Meyer et al, 2002). A robust result concerning the predictive power of the three components that has been pointed out by Meyer & Herscovitch (2001) and confirmed by the meta-analysis of Meyer et al (2002) is that "compared to continuance and normative commitment, affective commitment (a) correlates significantly with a wider range of "outcome" measures and (b) correlates most strongly with any given outcome measure" (Meyer & Herscovitch, 2001, p. 311).…”
Section: Affective Commitmentmentioning
confidence: 99%
“…Among the various definitions present in the literature, Meyer & Allen (1991) provided a successful three-component characterization of organizational commitment that has been extensively tested and refined (Meyer, Allen & Smith, 1993;Hackett, Bycio & Hausdorf, 1994). According to this approach, commitment can be defined as a general force that binds an individual to the organization but that has a complex and multifaceted structure consisting of three components (Meyer & Herscovitch, 2001).…”
Section: Affective Commitmentmentioning
confidence: 99%
“…Normative commitment reflects a feeling of obligation to the company. Strong commitment in this situation is where employees feel they ought to remain with the company based on a sense of duty, loyalty or moral obligation [21] . Meyer et al found that affective, normative and continuance commitments were distinguishable, but affective and normative commitments appear to be related [22] .…”
Section: Introductionmentioning
confidence: 99%
“…The multidimensionality of organisational commitment is now wellestablished Meyer, Allen, & Gellatly, 1990;Dunham, Grube, & Castañeda, 1994;Hackett, Bycio, & Hausdorf, 1994;McGee & Ford, 1987;Meyer, Allen, & Smith, 1993;Reilly & Orsak, 1991;Shore & Tetrick, 1991). Meyer, et al (1993) believed that, just as organisational commitment was best explained by three distinct component measures; professional commitment should similarly be explained by three distinct component measures.…”
mentioning
confidence: 99%